SOWING PERIOD AND ESTIMATED MAIZE PRODUCTION FOR SILAGE UNDER TROPICAL CONDITIONS - MELO, MARINA LUCIANA ABREU DE; CAMILO, JENNIFER ALVES; ANDRADE, CAMILO DE LELIS TEIXEIRA DE; AMARAL, TALES ANTÔNIO; SOUZA, ISABEL REGINA PRAZERES DE; SIMEÃO, ROSANGELA MARIA (REVISTA BRASILEIRA DE MILHO E SORGO, 2022)
In Brazil, livestock activity is affected by the seasonality of forage supply, which depends on the distribution of rainfall. The use of silage is one of the strategies to solve the problem during the annual dry season. The objective of this study was to use modeling to assess the productivity and quality of the maize silage in the state of Minas Gerais, Brazil. The CSM-CERES-Maize model was used to simulate maize silage production in 18 counties, at 52 sowing dates distributed throughout the year, with and without the use of irrigation. Absence of rainfall during the harvest period was also used as criterion to define the best sowing date in each county. In general, the best sowing dates were concentrated in October and February, respectively, for rainfed water supply and irrigated condition. The maize silage productivity under rainfed condition presented greater interannual variability and lower quality in comparison to that obtained under irrigated conditions. Under optimal soil-water conditions, climatic factors such as temperature and solar radiation are determinant to crop performance.